Derivations of simple three-dimensional anticommutative algebras - Pchelintsev, Sergey V.; Dubrovin, Maxim S. (Journal of the Belarusian State University. Mathematics and Informatics, 2024)
In this paper, we investigate the derivation algebras of simple three-dimensional anticommutative algebras over algebraically closed fields. The main statement of the article is that the derivation algebras of simple three-dimensional anticommutative algebras have dimensions 0, 1 and 3, for the latter case they are isomorphic to a simple Lie algebra of traceless matrices of the 2nd order.